2022
DOI: 10.2478/fhort-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Waste apple wood: A safe and economical alternative substrate for the cultivation of Pleurotus ostreatus and Lentinula edodes

Abstract: The use of waste apple-wood as a source of sawdust to cultivate the mushrooms Pleurotus ostreatus and Lentinula edodes is a common practice, but it is imperative to ensure that the wood does not contain unsafe amounts of heavy-metals or pesticide residues. In this study, we sampled and investigated the pollution of heavy metals and pesticide residues in apple-wood from Yantai, Shandong, China and cultivated P. ostreatus and L. edodes using apple-wood as substrate. Heavy metals, pesticide residues, mineral elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Biological yields obtained from the various tested substrates were comparable, except for VIP, and ranged between 0.42 on OS-VIP:1-1 and 0.59 kg on oak sawdust. On an experimental scale, Yu et al [ 55 ] reported a higher biological efficiency on oak sawdust (80.8 %), and Leifa et al [ 56 ] reported a different range of 78.4–85.8 % on various lignocellulosic substrates. Baktemur et al [ 15 ] reported biological efficiency values of 45.0, 65.7, and 21.3 % on substrates composed of oak sawdust, VIP, and VIP-OS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Biological yields obtained from the various tested substrates were comparable, except for VIP, and ranged between 0.42 on OS-VIP:1-1 and 0.59 kg on oak sawdust. On an experimental scale, Yu et al [ 55 ] reported a higher biological efficiency on oak sawdust (80.8 %), and Leifa et al [ 56 ] reported a different range of 78.4–85.8 % on various lignocellulosic substrates. Baktemur et al [ 15 ] reported biological efficiency values of 45.0, 65.7, and 21.3 % on substrates composed of oak sawdust, VIP, and VIP-OS, respectively.…”
Section: Resultsmentioning
confidence: 99%